STRATEGIES FOR A SELF-SELECTED UNANTICIPATED CHANGE OF DIRECTION MANEUVER AND THE RISK FOR ACL INJURY: FINDINGS FROM HAIE STUDY (Kinesiology, 2024)
The purpose of the study was twofold: 1) to qualitatively investigate the different change of direction (COD) strategies used by females in an ecological situation; and 2) to evaluate the knee internal adduction moment and knee flexion during the first 30% of support as risk factors for anterior cruciate ligament (ACL) injury during these strategies. Ninety-four females, classified in ACTIVE and NON-ACTIVE groups performed five trials of a COD maneuver that were subsequently qualitatively evaluated. Kinematic and ground reaction force data were analyzed in the first 30% of support. To assess differences between strategies, we used a two-way repeated measures analysis of variance. Four strategies of 45° COD maneuvers were found. The different strategies involved either a cross-over with the right or left leg or had no cross-over. The statistical analysis revealed significant differences with a lesser knee internal adduction moment (p